Antimicrobial test of five ethnomedicinal plants in an ancestral forest area - M.B. Bandibas; P. Roxas (Global Journal of Environmental Science and Management)
The basic premise of this research was to assess the ethnomedicinal uses of plants in an ancestral forest area at Naawan, Misamis Oriental and determine its inhibition effect against bacterial strains. The assessment of plants was conducted using the transect-plot method. Ethnomedicinal uses and the mode of preparations were obtained using a semi-structured interview questionnaire. Five ethnomedicinal plants: Crinum asiaticum L., Pavetta indica L., Bauhinia purpurea L., Mollugo pentaphylla L., and Cinnamomum mercadoi S. Vidalwere selected for the anti-microbial test against cultured bacterial strains; the Escherichia coli and Staphylococcus aureus using the disc diffusion method. These species are commonly used by the indigenous people and known to cure stomach disorder and wounds. The mode of preparation of the extracts follows the traditional method of the indigenous people. Chloramphenicol, on the other hand, was used as positive control. Thirty-three out of 61 identified species were locally claimed to have medicinal value and are known to cure stomach disorders, poisoning, bleeding, cough, fever and wounds, among others. Antimicrobial test showed greater inhibitory effect of Pavetta indica and Bauhinia purpurea against Staphylococcus aureus and Escherichia coli, correspondingly; however, the synthetic chloramphenicol exhibited greater antibacterial action than any of the plant extracts. In areas where civilization is afar, importance of forest in terms of medicinal uses is highly acknowledged by the local community. Indigenous people, in particular, know the importance of the forest especially in relation to health care system and they believe that there is a need to conserve the resources to sustain the services it provides.